The Presidents of the French Fifth Republic - Bell, D. author. aut Link
XVI, 219 p.
Keywords: In the French Republic political leadership is normally provided by the presidency, albeit from a very narrow constitutional base. This volume examines the strengths and weaknesses of that leadership as well as the way that executive power has been established in the republican context.